POLA PEMASARAN IKAN PATIN (Pangasius sp.) DI PASAR JAKABARING KOTA PALEMBANG - Sari, Lia Perwita; Utpalasari, Rih Laksmi (Universitas Muhammadiyah Palembang, 2019)
ABSTRACT The purpose of this study is to determine the pattern of Catfish (Pangasius sp.) marketing in Palembang City. The research method uses the survey method. The location of the study was determined intentionally (purposive), namely in Palembang Jakabaring Market. The research sample was taken using the accidental sampling method. Taking respondents through this method are collectors, retailers I, retailers II and housewife consumers who buy Catfish found at the research location to ask their opinions about what is needed for the smooth running of this research. The sample size of consumers in this study was set as many as 40 people, each 10 respondents in each cluster. Data collected in the form of primary data and secondary data. Data were analyzed descriptively qualitative and quantitative. Catfish (Pangasius sp.) is one of the local wisdom products from South Sumatra. High public consumption of Patin fish (Pangasius sp.) causes the marketing of Catfish (Pangasius sp.) in Jakabaring Market to vary from the activities of collecting traders to consumers. The large number of collectors and retailers is very influential on Patin fish (Pangasius sp.) distribution channels to reach the consumer level so that three different marketing patterns are formed in Jakabaring Market. The purpose of this study is to determine the pattern of Catfish (Pangasius sp.) qualitative descriptive. Researchers used a qualitative method by analyzing the characteristics of each respondent and the pattern of Catfish marketing in Palembang's Jakabaring Market. The results of the study stated that there were three patterns of Catfish marketing in the Jakabaring Market, namely pattern 1: Collector Traders - household consumers, Pattern 2: Collector Traders - Retailer Traders I, and Pattern 3: Collector Traders - Trader Retailers II.ABSTRAK Tujuan dari penelitian ini untuk mengetahui pola pemasaran ikan patin di kota Palembang. Metode penelitian menggunakan metode survei. Lokasi penelitian ditentukan secara sengaja (purposive) yaitu di Pasar Jakabaring Palembang. Penarikan sampel penelitian dilakukan dengan menggunakan metode accidental sampling. Pengambilan responden melalui metode ini adalah pedagang pengumpul, pedagang pengecer I, pedagang pengecer II dan konsumen ibu rumah tangga pembeli ikan Patin yang dijumpai dilokasi penelitian untuk meminta pendapat mereka mengenai hal yang dibutuhkan untuk kelancaran penelitian ini. Besar sampel konsumen dalam penelitian ini ditetapkan sebanyak 40 orang, masing-masing 10 orang responden di setiap cluster. Data yang dikumpulkan berupa data primer dan data sekunder. Data dianalisis secara deskriptif kualitatif dan deskriptif kuantitatif. Peneliti menggunakan metode kualitatif yaitu dengan cara menganalisis karakteristik masing-masing responden dan pola pemasaran ikan patin di Pasar Jakabaring Palembang. Hasil penelitian menyatakan bahwa terdapat tiga pola pemasaran ikan Patin di Pasar Jakabaring, yaitu pola 1 : Pedagang Pengumpul – konsumen rumah tangga, Pola 2 : Pedagang Pengumpul – Pedagang pengecer I, dan Pola 3 : Pedagang Pengumpul – Pedagang pengecer II.